Binnenwanderung und Städtewachstum in Japan - Schöller, Peter (ERDKUNDE, 1968)
The process of urban growth in Japan is analysed with tables and maps of internal migration structure, variations in the city-system by size groups and the directions of population movement. The results show a clear distinction of areas of mobility and regional arrangements in the form of population districts supplementary to the big cities. In general, we can find a fast expansion of the outer Metropolitan Areas, increase of inter-city migration and pre dominance of the Capital Region. In modern Japan, the pull-factor of internal migration seems more important than the push-factor of overpopulated districts. The reasons for migration and the problems of the attractiveness of big cities are discussed in the case of Tokyo. There are some indicators that the fast economic growth of Japan since 1955 cannot be understood without the size of internal migration and rapid urban development being taken into account.